Impacts of information atomization through social media algorithm manipulation in the legal domain: Analysis of the 'Brasil Paralelo' phenomenon - Mamedes, Mateus (2024)
The dispute over the field of truth is an inseparable part of the political phenomenon. With the advent of the internet and social media, the dynamics of modern sophistical combat have evolved, acquiring such complexity in the digitized environment. Thus, falsehood, as a strategic mechanism for mass manipulation, has been algorithmically transformed and sold as a virtual commodity. In this way, this work is dedicated to addressing the following issue: what are the impacts caused by the fragmentation of information through the manipulation of social media algorithms in the legal realm, based on the analysis of the 'Brasil Paralelo' phenomenon? Therefore, the general objective of the work is to analyze the impacts caused by the fragmentation of information through the manipulation of social media algorithms in the legal field, based on the analysis of the "Brasil Paralelo" phenomenon. The specific objectives are: to understand how algorithms function and how they are used by the 'Brasil Paralelo' company to segment the audience; to analyze the consequences of information fragmentation due to disinformation propagated by the 'Brasil Paralelo' company during the 2018 presidential elections, from a legal perspective; and to study strategies for addressing the challenges posed by disinformation caused by the manipulation of truth in the digital realm. To this end, the research sample space has been delimited to the productions of the 'Brasil Paralelo' company. This work follows an inductive method with a qualitative approach, primarily being an exploratory study through literature review. In conclusion, this work advances in providing focused reflections on an extremely relevant topic that still faces difficulties in terms of debate.